AUSGeoid98 geoid model of Australia: data treatment, computations and comparisons with GPS-levelling data - Featherstone, Will; Kirby, Jon; Kearsley, A.; Gilliland, J.; Johnston, G.; Steed, J.; Forsberg, R.; Sideris, M. (Springer Verlag, 2001)
The AUSGeoid98 gravimetric geoid model of Australia has been computed using data from the EGM96 global geopotential model, the 1996 release of the Australian gravity database, a nationwide digital elevation model, and satellite altimeter-derived marine gravity anomalies. The geoid heights are on a 2 by 2 arc-minute grid with respect to the GRS80 ellipsoid, and residual geoid heights were computed using the 1-D fast Fourier transform technique. This has been adapted to include a deterministically modified kernel over a spherical cap of limited spatial extent in the generalised Stokes scheme. Comparisons of AUSGeoid98 with GPS and Australian Height Datum (AHD) heights across the continent give an RMS agreement of -0.364 m, although this apparently large value is attributed partly to distortions in the AHD.